The Emergency Department Response to Women Experiencing Intimate Partner Violence: Insights From Interviews With Clinicians in Australia. (25th March 2019) - Dawson, Angela J.; Rossiter, Chris; Doab, Anna; Romero, Bernadine; Fitzpatrick, Lesley; Fry, Margaret
Abstract: Background and Objectives: Emergency departments (EDs) are essential providers of compassionate, immediate treatment and referral for women experiencing intimate partner violence (IPV). IPV, largely perpetrated by men against women, exerts a substantial burden on the health systems and economies of all nations. There is little known about how staff in Australian EDs respond to the challenges such violence generates. We therefore examined the clinical team response to women experiencing IPV in two large Australian metropolitan hospital EDs. Methods: We undertook qualitative semistructured interviews and focus group discussions with 35 social workers, nurses, and doctors. Transcripts were recorded and transcribed verbatim. We analyzed the data thematically. We first undertook line‐by‐line coding and organized content into descriptive categories. Latent and manifest patterns were identified across the data and mapped to key themes in negotiation with all authors. Results: Respondents emphasized challenges identifying IPV resulting from professional uncertainty or discomfort and women's fear of the ramifications of disclosure. Emergency clinicians routinely referred women to social workers after medical treatment and described effective collaboration across professions. Social workers outlined difficulties coordinating care with health and community agencies. Staff highlighted challenges maintaining nonjudgmental attitudes and managing their own feelings—especially clinicians who had personally experienced violence. Conclusions: Emergency departments can provide caring environments for women experiencing IPV. Effective interprofessional teamwork across nursing, medical, and social work professionals may mitigate the need for formal screening tools. Supportive workforce environments can improve staff understanding, reduce stigma, enhance appropriate treatment, and counsel health professionals experiencing violence. However, staff training and advocacy and referral relationships with local programs require strengthening. A connected multisystems‐level response is required to coordinate and resource services for all affected by violence.